Islamic Education and the Promotion of Societal Values in Indonesia: A Critical Analysis of Curricula, Pedagogical Practices, and School Culture - Barry, Aboubacar; Diallo, Thierno Dardaye; Diallo, Thierno Abdoul Goudous; Yousef, Hateenah Ali Sulaiman (The Magister of Islamic Education IAIN Pontianak, 2026)
This research rigorously analyzes how Islamic education serves to promote value-based education in Indonesia through curriculum, pedagogy, and school culture. In particular, the study hopes to understand how educational practices based on Islamic principles contribute to the students' moral disposition, civic obligations, and sense of belonging to a diverse society. A qualitative documentary method (focused on textual and curricular analysis of Qur’anic principles, classical writings, and recent educational literature) was employed in the study, examining how Islamic values were conveyed and emphasized through formal lessons.The research results point to cultural aspects of Islamic education playing a major role in developing the moral self by emphasizing and cultivating an ethical climate, quality, and character of a school. Teachers will lead as role models that are ethical, school working structures will reinforce values such as honesty, caring, respect, & taking responsibility. A school will provide students with opportunities to connect with morals through storytelling, reflection, service-learning experiences, and communal worship opportunities, which support cognitive change and emotional growth. In addition, Islamic education will enhance social harmony through robust processes of tolerance, and intercultural knowing and understanding, employing ethical frameworks and discourses of understanding. Results suggest that Islamic education can augment developmental learning for ethical citizens, so long as it pathways to both traditional and recent pedagogical understandings. These insights have profound implications for curriculum developers, educators, and policymakers dedicated to improving the societal relevance of religious education in modern, pluralistic societies.